Viscous Behavior of PS, PP, and ABS in Terms of Temperature and Pressure-Dependent Hole Fraction - TAV, CUMALİ; YAHŞİ, UĞUR (JOHN WILEY & SONS INC, 2010)
We have developed a zero-shear viscous model in terms of temperature- and pressure-dependent hole fraction computed from Simha-Somcynsky Hole Theory. This model successfully interprets the viscosity data of PS, PP, and ABS as a function of hole fraction for a broad range of temperature and pressure. We have also introduced and discussed a new term: Viscoholibility; the derivative of logarithm of viscosity with respect to hole fraction. When the hole fraction takes highest available value, the viscoholibility approaches asymptotically to a constant value by which the viscosity changes linearly with the hole fraction. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 117: 110-113,2010
Keywords: zero-shear viscosity; free volume; hole fraction; Simha Somcynsky hole theory; equation of state; MOLECULAR-WEIGHT HYDROCARBONS; VACANCY BEHAVIOR; POLYMER MELTS; FREE-VOLUME; VISCOSITY; LINKING; THERMODYNAMICS